The Risotto sign – a severe inflammatory bursitis with rice body formation, complicating a rotator cuff repair with a bioabsorbable suture anchor. (19th January 2015) - Sivaloganathan, Sivan; Amr, Romel; Shrivastava, Raj; Relwani, Jaikumar
Lesson: There is an association between inflammatory bursitis with rice body formation and use of bioabsorbable suture anchors.